Bicaudate ratio as a measure of caudate volume on MR images. - Aylward, E H; Schwartz, J; Machlin, S; Pearlson, G (American Journal of Neuroradiology, 1991)
Many studies have used ratios based on intercaudate distance as a measure of caudate atrophy and ratios based on bifrontal distance as a measure of ventricular enlargement independent of caudate atrophy. The purpose of the current study was to determine to what extent these ratios correlate with caudate area and volume and frontal horn area in various groups of patients. The three linear ratio measures, obtained from MR scans, were bicaudate ratio, bifrontal ratio, and bifrontal distance divided by bicaudate distance. Area and volume measures were corrected for brain size. Subjects included patients with autism, obsessive-compulsive disorder, and Huntington disease, as well as normal controls. As expected, the patients with Huntington disease had the largest bicaudate ratio, bifrontal ratio, and frontal horn area. Both bicaudate ratio and bifrontal ratio were fairly good measures of frontal horn size for most groups. Consistent with theoretical expectations, the bifrontal ratio was not highly correlated with caudate area or volume ratios. Bicaudate ratio and bifrontal distance/bicaudate distance were correlated with caudate volume for the patients with Huntington disease, but not for any of the other groups. Bifrontal distance/bicaudate distance was the best single predictor of caudate volume for all groups combined. It is concluded that bicaudate ratio and bifrontal distance/bicaudate distance are fairly good measures of caudate atrophy, but are poor measures of caudate size when no atrophy is present.